Innovación en los procesos de comercialización y su incidencia en la competitividad del sector cárnico en Machala, 2025 - Amaya Pantaleon, Herman Raul (Machala : Universidad Técnica de Machala, 2025)
The study “Innovation in Marketing Processes and Its Impact on the Competitiveness of the Meat Sector in Machala, 2025” examines how technological innovation strengthens the competitiveness of sausages and meat products in Machala. In a context of digitalization, demanding consumers, and sustainable markets, it evaluates the adoption of social media, e-commerce, QR codes, and traceability among small and medium-sized enterprises. Methodologically, the study uses a mixed approach: surveys of 50 retailers and 150 consumers, along with interviews with key stakeholders. The findings show growing interest in digitalization, but persistent barriers related to limited knowledge, financial constraints, and distrust of online sales. Even so, many consumers would purchase online if quality, food safety, and payment security are guaranteed. The hypothesis is partially confirmed: innovation improves competitiveness when accompanied by training, institutional support, and clear strategies. The use of digital tools—even basic ones—increases visibility, loyalty, and reach. Actions are recommended for retailers, the public sector, and academia: free training, partnerships, and the development of sales and after-sales channels. The study concludes that transforming the sector requires a comprehensive approach that integrates sustainability, technology, and training to meet new market demands. Digitalization is not only a technical necessity but also a strategic opportunity to position local meat products and scale their competitiveness nationwide.
La investigación “Innovación en los procesos de comercialización y su incidencia en la competitividad del sector cárnico en Machala, 2025” analiza cómo la innovación tecnológica fortalece la competitividad de embutidos y carnes en Machala. En un contexto de digitalización, consumidores exigentes y mercados sostenibles, se evalúa la adopción de redes sociales, comercio electrónico, códigos QR y trazabilidad en pequeñas y medianas empresas. Metodológicamente, el estudio emplea un enfoque mixto: encuestas a 50 comerciantes y 150 consumidores, más entrevistas a actores clave. Los hallazgos muestran interés creciente por digitalizar, pero persisten barreras de desconocimiento, limitaciones financieras y desconfianza hacia la venta en línea. Aun así, muchos consumidores comprarían por internet si se garantiza calidad, inocuidad y seguridad de pago. La hipótesis se confirma parcialmente: la innovación mejora la competitividad cuando se acompaña de capacitación, apoyo institucional y estrategias claras. El uso de herramientas digitales, incluso básicas, incrementa visibilidad, fidelización y alcance. Se recomiendan acciones para comerciantes, sector público y academia: formación gratuita, alianzas y desarrollo de canales de venta y postventa. Se concluye que la transformación del sector exige un enfoque integral que articule sostenibilidad, tecnología y formación para responder a nuevas exigencias del mercado. La digitalización no es solo necesidad técnica, sino oportunidad estratégica para posicionar los productos cárnicos locales y escalar su competitividad nacional.
Keywords: INNOVACIÓN COMERCIAL; TRANSFORMACIÓN DIGITAL; SECTOR CÁRNICO; PYMES